Electronic structure and STM images simulation of defects on hBN/ black-phosphorene heterostructures: A theoretical study (2018)
By first principles calculations which include van der Waals interactions, we studied the electronic structure of hexagonal boron-nitride/black-phosphorene heterostructures (hBN/BP). In particular the role of several kind of defects on the electronic properties of black-phosphorene monolayer and hBN/BP heterostructure was analyzed. The defects under consideration were single and double vacancies, as well Stone-Wale type defects, all of them present in the phosphorene layer. In this way, we found that the electronic structure of the hBN/BP is modified according the type of defect that is introduced. As a remarkable feature, our results show occupied states at the Fermi Level introduced by a single vacancy in the energy gap of the hBN/BP heterostructure. Additionally, we performed simulations of scanning tunneling microscopy images. These simulations show that is possible to discriminate the kind of defect even when the black-phosphorene monolayer is part of the heterostructure hBN/BP. Our results may help to discriminate among several kind of defects during experimental characterization of these novel materials. © 2017 Elsevier B.V.